Effects of gender norms on intelligence tests: Evidence from ASIS - Deniz Arslan; Ömer Faruk Tamul; Murat Doğan Şahin; Ugur Sak (Journal of Pedagogical Research, 2023)
An examination of gender-related differential item functioning was conducted on the verbal subtests of the Anadolu-Sak Intelligence Scale. Analyses were conducted using the scale standardization data (N = 4641). A Mantel-Haenszel statistic was used to detect differential item functioning (DIF). A total of 58 verbal analogical reasoning items, 20 verbal short-term memory items, and 70 vocabulary items were analyzed. Initially, items displaying DIF in different age groups were determined, and then experts were consulted to determine whether these items were biased. There were three items with item effects on the Verbal Analogical Reasoning subtest and five items on the Vocabulary subtest. Short-term Memory subtests did not reveal any bias. Several implications regarding cognitive development, gender perceptions, and cultural factors were discussed.